A Study on the Influence of Classroom Language Environments on Vocabulary Semantic Development in Preschool Children - WangQing, (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
The complexity of classroom language environments significantly influences the systematic construction of preschool children’s lexical-semantic systems. With advances in neurolinguistics and social interaction theories, educational researchers increasingly focus on the long-term effects of early language input quality on children’s cognitive development. Findings indicate that current academic discourse primarily focuses on the following dimensions: first, the mechanisms through which language environments influence lexical development; second, the mechanisms through which language environments influence lexical development; third, the systematic integration of environmental factors; and fourth, the systematic integration of environmental factors. Despite the positive trend of diverse perspectives and expanded content in current research, systemic deficiencies persist. Research perspectives remain relatively homogeneous, with insufficient attention to environmental dynamics; studies on micro-level mechanisms lack depth and yield limited teaching application outcomes; research on cultural adaptability and individual differences exhibits significant shortcomings. Consequently, future research should broaden and deepen its scope, prioritizing the differential characteristics of language interaction across diverse cultural backgrounds and educational settings; strengthen the organic integration of empirical research and theoretical innovation; rigorously validate findings; and strive to construct a scientifically effective language support system for preschool education, achieving systematic optimization in environmental design, teacher–child interaction, curriculum development, and assessment feedback. These explorations will provide a solid theoretical foundation and actionable practical solutions for enhancing the appropriateness and effectiveness of language environments in preschool education.